2022
DOI: 10.1101/2022.10.18.512680
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanical management of weeds drops nymphal density ofXylella fastidiosavectors

Abstract: Xylella fastidiosaWells (1987) (Proteobacteria:Xanthomonadaceae) is a xylem pathogen bacterium transmitted by xylem feeder insects that causes several important plant diseases such as Pierce’s disease in grapes or leaf scorch in almond and olives trees. The bacterium was detected in the Balearic Islands in October 2016, including three subspecies:fastidiosa,multiplexandpauca. The major potential vectors described in the Balearics arePhilaenus spumariusL. andNeophilaenus campestrisFallen (1805). In order to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Interestingly, we also show that acting on the vector removal μ is more effective than controlling the newborn vector population N v (0). In fact, most control strategies carried out in practice for Xf diseases focus on the latter factor, reducing N v (0) via egg or nymph control (Cornara et al 2018; López-Mercadal et al 2022). However, our results indicate that alternative strategies based on increasing the removal (or dispersal) rate of vectors should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we also show that acting on the vector removal μ is more effective than controlling the newborn vector population N v (0). In fact, most control strategies carried out in practice for Xf diseases focus on the latter factor, reducing N v (0) via egg or nymph control (Cornara et al 2018; López-Mercadal et al 2022). However, our results indicate that alternative strategies based on increasing the removal (or dispersal) rate of vectors should be explored.…”
Section: Discussionmentioning
confidence: 99%
“…The control of spittlebug populations in Apulia relies on mechanical treatments, such as tillage and mowing, to kill nymphs in spring, and application of insecticides on olive trees against the adult stage (EFSA Panel on Plant Health (PLH) et al 2019;Sanna et al 2021;Morelli et al 2021;EU 2020EU /1201. While the effectiveness of agronomic measures in reducing spittlebug populations in the field is demonstrated (EFSA Panel on Plant Health (PLH) et al 2019;Sanna et al 2021;López-Mercadal et al 2022), the impact of insecticidal treatments on vector density remains unclear. Indeed, several issues with the use of insecticides against spittlebugs are currently present, among them: i) few active ingredients available, also due to the recent banning of some neonicotinoids, the most effective chemical family of insecticide against P. spumarius (Dongiovanni et al 2018), ii) quite low persistence of available insecticides, such as organophosphates and Spinosad (Dáder et al 2019), iii) high densities of both nymphal and adult stage in semi-natural reservoirs (Bodino et al 2019;Cornara et al 2021;Cappellari et al 2022); iv) adult spittlebugs exposed to insecticides could present sublethal effects and/or active movements (flight), possibly impairing the effectiveness of control measures to on disruption of Xf transmission (Bodino et al 2020;Lago et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Sanna et al (2021) reported that tillage practices can reduce P. spumarius density by 60%, while frequent mowing can reduce the density by 20%. López-Mercadal et al (2022) also reported that tillage and mowing significantly decreased the nymphal density of X. fastidiosa vectors in the olive grove and vineyards. The negative effect of tillage on the population of P. spumarius was related to the high direct mortality of juveniles combined with the complete removal of the herbaceous vegetation (Sanna et al, 2021).…”
Section: Chaptermentioning
confidence: 87%